Referenciação e humor: uma investigação acerca do processo de recategorização em charges de cunho político veiculadas no Instagram - Kéticia Lhirrozi Bueno Alves de, Souza (2021)
Apothéloz and Béguelin (1995) and Neves (2006) postulate that recategorization is performed when a referent receives an initial designation in the text and after that is resumed in other ways during the communicative activity. The studies and theories of these authors are valuable for the understanding of referencing, and consequently, of the referential resource of recategorization. However, they describe the use of this feature from oral and/or written texts. Thus, there is still room to study the process of referencing in multimodal texts. In view of this, realizing the vast number of interactions mediated by the computer and noting that individuals have relied on the use of multimodal texts, such as cartoons, to express their opinions on issues of social relevance, such as politics, the question was asked: How has the recategorization resource been used as a linguistic-discursive and semiotic strategy in the process of referencing and production of humor in cartoons? To answer this question, we sought theoretical grounding in authors such as Flôres (2002), Lakoff and Jhonson (2003), Barton and Lee (2015), Koch (2018), among others. Moreover, it was established that the general objective of this research is to analyze the recategorization resource in the process of referencing and production of humor in political cartoons, published in humor pages on Instagram in the years 2019/2020, and that the specific objectives are i) to understand the function - within the text and context - of the use of the recategorization strategy and ii) to discuss the semantic relations activated from the recategorizations exposed in the cartoons. To answer the questions and meet the proposed objectives, a qualitative-exploratory approach was adopted; furthermore, descriptive-interpretative analyses of four political cartoons, published in humor pages on Instagram, were carried out. The data analysis showed that the recategorization in cartoons does not happen in a linear way as it can occur in other texts that are constituted primarily by verbal semiosis, and that many are the factors involved in the process of recategorization of referents, among these factors are included mental processes that are activated during the production of meanings.